تطور كتابة قصة سيدنا يوسف عليه السلام في الأدب الملايوي وتأثره بالأدب العربي = Story evolution of the Prophet Joseph Peace Be Upon Him in Malay literature and effect of Arabic literature - Din, Rosma; Yaacob, Adli (2021)
This research deals with an evolution writing the story of Prophet Yusuf (Peace Be Upon Him) in Malay literature both ancient and modern. The story is featured in many manuscripts, history books and interpretation of Quran as named in the poets. In addition, there are studies and researchs to reveal his character, beauty, patience towards each trial in at all stages of life and success in solving the economic crisis when he was appointed prime minister of Egypt. This research aims to collect the bulk of what has been written about this noble Prophet in Malay literature in poetry and prose also to reveal an evolution in the writing of this story. The research is based on the descriptive approach, through the study of specific books to search for the story of The Prophet Joseph poetic and proses. Research also uses an analytical approach to discuss and analyze from relevant views. The researcher notes that writing Prophet Yusuf story is a continuous process through an ages; the poets, authors, interpreters and researchers wrote about this story. Some directors have directed series adapted from his story. The interpreters and historians, the whole story was narrated, including those who draw the novel from the Israelis and some who distinguish it from the correct ones and most poets also authors focus on the love of a woman named Zulaikha.